2014
DOI: 10.1177/0042098014529343
|View full text |Cite
|
Sign up to set email alerts
|

Forty years of immigrant segregation in France, 1968–2007. How different is the new immigration?

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 44 publications
(54 reference statements)
1
10
0
Order By: Relevance
“…All in all, this evidence suggests that residential segregation in France is maintained in part by an interconnected process of low mobility among immigrants and their offspring out of coethnic neighbourhoods, coupled with the increased mobility of the French majority out of immigrant neighbourhoods. These findings bring new substance to the debate on urban inequality in France, which has tended to oppose two paradigmatic representations of segregation: hypersegregation dividing blacks and whites in the United States (Massey & Denton, ; Wilkes & Iceland, ) versus ethnoracially diverse European cities where spatial disadvantage is less intense (Musterd, ; Pan Ké Shon & Verdugo, ; Wacquant, ). Due to data comparability issues between immigrants in France and ethnic/racial groups in the United States, this debate has been difficult to resolve.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…All in all, this evidence suggests that residential segregation in France is maintained in part by an interconnected process of low mobility among immigrants and their offspring out of coethnic neighbourhoods, coupled with the increased mobility of the French majority out of immigrant neighbourhoods. These findings bring new substance to the debate on urban inequality in France, which has tended to oppose two paradigmatic representations of segregation: hypersegregation dividing blacks and whites in the United States (Massey & Denton, ; Wilkes & Iceland, ) versus ethnoracially diverse European cities where spatial disadvantage is less intense (Musterd, ; Pan Ké Shon & Verdugo, ; Wacquant, ). Due to data comparability issues between immigrants in France and ethnic/racial groups in the United States, this debate has been difficult to resolve.…”
Section: Discussionmentioning
confidence: 97%
“…In France, urban inequalities impacting immigrants and their offspring have been a growing focus of debate in the media, in politics, and in the social sciences. Although research on the question is not widespread, existing findings provide broad support that spatial outcomes vary significantly by immigrant origin, showing the highest levels of segregation between natives and non‐Europeans (Pan Ké Shon & Verdugo, ; Préteceille, ; Safi, ). As in most Western societies, the spatial concentration of immigrants is associated with socio‐economic disadvantage, high unemployment, crime, lower quality schools, and public housing (Tissot & Poupeau, ) and is symbolically linked with the failure of the French state to integrate immigrants, as well as the alleged self‐segregation of minorities who are perceived to refuse to assimilate (Lagrange & Oberti, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has shown that the generous and universal Nordic welfare system has an equalizing effect on all population subgroups; ethnic minorities are relatively well integrated into education and the labor market in those countries, and levels of residential segregation are relatively low (Bevelander ). Welfare state policies have likely reduced differences between population subgroups in the UK and France; however, the size of the main minority groups is large in those countries and residential and school segregation is high, particularly in the UK (Musterd ; Pan Ke Shon and Verdugo ). These factors certainly promote minority subcultures in those countries and reinforce specific family patterns—for instance, through high levels of ethnic intermarriages.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…This is in contrast to a number of international studies that have called attention to declining levels of segregation based on trends in the dissimilarity index (Frey 2014; Shon and Verdugo 2015; Simpson 2007). Since assessing segregation trends is such an important issue, both academically and politically, a critical perspective on the methods used in such studies is warranted.…”
Section: Background: Changing Ethnic Residential Segregation Patternsmentioning
confidence: 59%